Practical Manual on Groundwater Quality Monitoring - Ravenscroft, Peter (Washington, DC: World Bank, 2022)
This is a companion volume to “Seeing the Invisible: A Strategic Report on Groundwater Quality,” which explains why groundwater quality is so important to managers of development programs in the World Bank and elsewhere. Its purpose is to provide managers and their teams with practical guidance on how to set up and manage a groundwater quality monitoring program. It provides a logical, step-by-step approach that can be tailored to, and grow with, the capacity to implement such a program. The guiding principle is that monitoring is the fundamental activity that shapes our identification of issues, the framing of problems, the design of solutions, and the measurement of the effectiveness of those solutions. Monitoring is often seen as simple and undervalued, but monitoring of groundwater quality, and its interpretation, is technically demanding. On the other hand, it is also extremely rewarding.